Male involvement in antenatal care follow-up and its determinants in Ethiopia: a systematic review and meta-analysis - Gossa Fetene Abebe; Desalegn Girma; Melsew Setegn Alie; Lidiya Gutema Lemu; Yilkal Negesse; Zewditu Alelign (BMJ Open)
Objective To determine the involvement of males in antenatal care (ANC) follow-up and its determinants in Ethiopia.Design A systematic review and meta-analysis.Data sources A systematic search was done on PubMed, African Journals Online, HINARI, ScienceDirect, Google Scholar and direct Google up to 20 November 2023.Eligibility criteria We included cross-sectional or case–control studies reporting male involvement in ANC service and its determinants in Ethiopia, which were published as full-length articles in English.Data extraction and synthesis The Joanna Briggs Institute checklist was used to appraise the included studies, and the I2 test was used to evaluate heterogeneity among the studies. We assessed publication bias using a funnel plot and Begg’s test. The forest plot presented the combined proportion of male involvement and OR, along with a 95% CI.Results The pooled proportion of male involvement in ANC follow-up in Ethiopia was 43.3% (95% CI 31.7% to 54.8%). Male partners with secondary education or higher (Adjusted Odds Ratio (AOR) 2.72, 95% CI 1.81 to 4.10), government employment (AOR 2.09, 95% CI 1.49 to 2.94), attendance at health education (AOR 3.02, 95% CI 1.39 to 6.54) and knowledge about ANC or pregnancy danger signs (AOR 2.36, 95% CI 1.33 to 4.19) demonstrated a significant association with increased male involvement.Conclusion Male involvement in ANC in Ethiopia is low. Recommendations include targeted education for males with no formal schooling, improved health education on ANC and pregnancy risks, and interventions for males in the private sector.PROSPERO registration number CRD42021258826.